Accuracy validation and bias assessment for various multi-sensor open-source DEMs in part of the Karakoram region. Issue 10 (2nd October 2020) - Kumar, Anant; Negi, H.S.; Kumar, Kamal; Shekhar, Chander
ABSTRACT: The present study evaluate horizontal and vertical accuracy of seven open-source digital elevation models (DEMs) having moderate-to-high resolutions viz. 30 m Shuttle Radar Topography Mission (SRTM1), Advanced Spaceborne Thermal Emission and Reflection Radiometer Global DEM (ASTER GDEM), Advanced Land Observing Satellite World 3D (AW3D30), and Cartosat DEM (CartoDEM), 90 m TerraSAR-X add-on for Digital Elevation Measurement (TanDEM-X), 12.5 m terrain corrected Phased Array L-band Synthetic Aperture Radar (PALSAR) from Advanced Land Observing Satellite (ALOS) and 8 m High Mountain Asia (HMA) over the rugged mountainous terrain of the Karakoram region. Horizontal accuracy (specified in x and y ) assessed by referring photogrammetrically generated master DEM from Cartosat-1 revealed AW3D30 as the most consistent DEM with a slight shift of +2.80 m and −4.89 m in x and y direction, respectively. However, vertical accuracy analysis showed that both HMA and AW3D30 DEMs are quite close to each other with MAE of 3.01 m and 3.46 m, RMSE of 5.6 m and 7.5 m, and NMAD of 4.09 m and 5.5 m, respectively. We also examined the influence of slope on DEM errors and associated elevation-dependent bias over non-glaciated surface which can be valuable input for geodetic mass balance estimations.